Strategi Dinas Ketenagakerjaan dalam Meningkatkan Kesempatan Kerja bagi Penyandang Disabilitas di Kabupaten Sidoarjo - Hariyanti, Kiki; Sukmana, Hendra (Mahesa Research Center, 2022)
This study aims to determine the Strategy of the Manpower Office in Increasing Employment Opportunities for Persons with Disabilities. The sampling technique in this study is snowball sampling technique. The approach in this study uses a qualitative approach with a descriptive method. Important insights were obtained through interviews and observations related to the strategy of the Sidoarjo Regency Manpower Office in developing the employment potential of persons with disabilities. Meanwhile, optional information is collected through reports such as Sidoarjo Disnaker Records, Related Domain Records, Principles and Regulations, Widely Communicated Data, Other Information and Data on the employment potential of persons with disabilities. The primary data was tried through the Triangulation Technique. The Triangulation technique used in this examination is to compare observational information and interview information and compare with the content of related documents. Â From the results of this study, it is shown by the results of interviews from various parties, that the provisions of the Sidoarjo Regency regulations on Persons with Disabilities are still not optimally determined. Â There are contributing factors that cause the employment opportunities of people with disabilities to be narrow, one of which is the low level of education.